Predictors of Senior High School Teacher's Job Satisfaction Level - Aseron, Delmark (Journal of Interdisciplinary Perspectives, 2024)
With the implementation of the Enhanced Basic Education Act of 2013, also known as Republic Act 10533 or K to 12, the Philippines initiated a curriculum change in its basic education system. This change extended the number of years in school from ten (10) to twelve (12), leading to the introduction of Senior High School. However, this alteration in the educational system posed challenges in maintaining job satisfaction among educators. Grounded in Herzberg's two-factor theory, this study aims to analyze the predictors of job satisfaction among Senior High School teachers in a private educational institution. Employing a quantitative research design, the study utilized the Job Satisfaction Survey to gauge the job satisfaction levels of these teachers. Data analysis involved T-tests and ANOVA. Results revealed that the satisfaction levels of respondents did not significantly differ, as indicated by a t-test probability value of 0.937, failing to reject the null hypothesis since 0.937 exceeds the significance level of 0.05. Thus, there was no significant difference in job satisfaction levels based on gender. However, educational attainment was found to predict differences in job satisfaction levels among senior high school teachers. Overall, the study suggests a significant relationship between job satisfaction levels and years of teaching experience among senior high school teachers